Secular Islam - Devji, F (Taylor and Francis, 2018)
While he appears to have been a relentless critic of secularism as a liberal ideal, the celebrated Indian poet and philosopher Mohammad Iqbal might also be considered among its more important non-European theorists. Globally one of the most influential Muslim thinkers of the twentieth century, Iqbal started publishing in its first decade, reaching the height of his power and popularity during the inter-war period until he died in Lahore in 1938. He studied philosophy as well as Arabic and Persian thought in Lahore, Cambridge, and Munich, and drew extensively upon European as much as Asian thinkers. I will argue here that Iqbal followed an important tradition of pre-modern philosophy by thinking about the relationship between politics and theology in esoteric terms.